One Does Not Simply Walk into Mordor: Sound and Music as Suture in the Opening Sequences of Peter Jackson's Middle-earth Films. - WHITE, DANIEL (Music, Sound & the Moving Image)
The opening sequences of narrative films are perhaps the most important moments for establishing a coherent film-world and drawing a viewer into a space and time often quite different from their own, and yet these moments remain largely untheorised within film studies and film music theory in particular. This article analyses the uses of music and sound in the opening sequences of Peter Jackson's Middle-earth trilogies: The Lord of the Rings (2001–2003) and The Hobbit (2009–2011). The paratextual nature of opening sequences might lead us to understand them as theoretical gateways or airlocks, but it is the psychoanalytical concept of suture that proves most effective in theorising music's dual roles in drawing an audience into a film-world and simultaneously building that world around them. This paper's motivic and harmonic investigation draws particularly on Scott Murphy's theories of transformational analysis to understand the different ways that musical language can be established as a form of cinematic suture.